Managerial Opinions on the Functions of Geographic Information Systems in Education Management and Planning in Türkiye: The Case of Elazığ - Akıllı, Ceyda; Polat, Yeliz; Kılınç, Fethi (My University, 2025)
A Geographic Information System (GIS) aims to store, interpret, query, design according to specific requirements, and make available to the public both digital and non-digital information, ensuring it is maintained in accordance with certain standards through planning, implementation, and process management. GIS is a system that brings together all geographic assets and information related to events, and is capable of updating this data, producing results, and generating alternative solution strategies. The aim of this study is to reveal the views of managers regarding the functions of GIS use in educational institutions in Türkiye in relation to educational planning and to provide a detailed data source on GIS. The phenomenological design was utilized in the research. The sample group of the research consisted of 23 education managers working in Elazığ, determined according to the maximum diversity sampling method. A semi-structured interview form was used as the data collection tool in the research. The data were analyzed using content analysis techniques. The results of the study revealed that participants stated that GIS facilitated data-based management and decision-making processes in the dimension of educational management. In the dimension of infrastructure planning, participants stated that GIS contributed to building and risk planning, while in the dimension of student affairs, they stated that it facilitated registration processes and increased access to education. In the human resources dimension, participants stated that GIS enabled the rational execution of employment and staffing plans, while in the education financing dimension, they stated that GIS facilitated the management of resources.
Keywords: Geographic Information Systems; Educational Management; Educational Organizations; Education Managers